Evaluation of Aggressive Behaviour Management in PICU (Psychiatric Intensive Care Unit): A Focus Group Study - Ah. Yusuf (Journal of Global Pharma Technology, 2020)
Background: PICU is a Psychiatric Intensive Care Unit. PICU is a service aimed at mental health clients in conditions of psychiatric crisis. PICU is a combination of psychiatric emergency services and intensive services, which can be held in psychiatric hospitals or psychiatric units in general hospitals. Purpose: This study is on evaluating aggressive problem management at PICU. Methods: This research was designed with a qualitative approach using focus group discussion. The total number of participants was 12 nurses. Data was collected using a focus group and analyzed using standard software NVIVO 12 Plus. This research was conducted from January to March 2020. Respondents consisted of Head of the room, Head of the nurses' team, Managing Nurse, and Supervisor. Results: This research was conducted to explore the experience of nurses in dealing with business class patients in commercial medical escorts. The results of this study found 3 themes, namely: rules are not systematic, injuries due to restrain are still high, nurses' competencies are not evenly distributed. Conclusion: several themes and sub-themes support nurses in treating aggressive client behavior. Besides, nurses must standardize services to improve patient and family satisfaction. Keywords: Aggressive behavior, Mental Disorder, Nurses, PICU.